Polskie wybory czeskiej prozy kobiecej w przekładach po 1989 roku - Żygadło-Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2018)
Polish Choices of Czech Female Prose in Translations after 1989 In the article we pay special attention to the presence of Czech female writing in Poland after 1989. In the latest Czech literature, women are becoming more and more significant. In recent years, books by Czech female writers, particularly of a young generation, have been translated. Based on Pierre Bourdieu’s theory of field, capital and habitus, the article is concerned with the role of a translator as an active agent in literary communication. KEY WORDS: Polish choices, Czech female prose, Pierre Bourdieu’s theory, translation, a translator